Case report of a rare glandular odontogenic cyst in a child: A diagnostic dilemma - Tavargeri, Anand K.; Anehosur, Venkatesh; Niranjan, K.C.; Nayyar, Amrita (International Journal of Health Sciences, 2019)
This paper reports a case of glandular odontogenic cyst (GOC) in a 12-year-old male patient. GOC is a rare entity occurring in the jaw bones. Known for its aggressive behavior and nonspecific clinical features, it may mimic other clinicopathological lesions such as botryoid odontogenic cyst and central mucoepidermoid tumor making the diagnosis challenging. It is more prevalent in the middle age adult population, and very few cases have been reported in children.